Factors leading to open revision surgery after trans-sacral canal plasty for lumbar spine disease - Arimura, Daigo; Shinohara, Akira; Katsumi, Shunsuke; Obata, Shintaro; Ikegami, Taku; Sawada, Naomu; Mori, Keiichiro; Saito, Mitsuru (Frontiers in Surgery, 2024)
Trans-sacral canal plasty (TSCP) is a minimally invasive lumbar spine surgery under local anaesthesia. TSCP is expected to be effective regardless of whether the patient has had previous surgery. However, there are cases in which open revision surgery is required after TSCP. This study aimed to identify risk factors for open revision surgery after TSCP in order to determine surgical indications and limitations. A retrospective case-control study was conducted in patients who underwent TSCP for lumbar spine disease. Data of 112 patients were analysed. During an observation period of 7-23 months, 34 patients (30.4%) required open revision surgery and 78 (69.6%) did not. The following patient background characteristics were investigated: age, sex, body mass index (BMI), diagnosis, history of spine surgery and the institution where the surgery was performed. Comorbidities were scored using the Elixhauser Comorbidity Index.Preoperative imaging parameters were investigated, including the lesion level (L4/5, L5/S1, other), presence of intervertebral instability, dural sac area, presence of bony stenosis and presence of epidural lipoma. Multivariate analysis revealed that intervertebral instability (odds ratio 2.56, confidence interval 1.00-6.51, p=0.046) and a narrow dural sac area (odds ratio 0.98, confidence interval 0.97-0.99, p=0.002) were significant risk factors for open revision surgery after TSCP.